1962
DOI: 10.1182/blood.v20.4.471.471
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Deficiency in the Monkey. IV. Further Studies of the Anemia with Emphasis on Bone Marrow Morphology

Abstract: Nuclear abnormalities were observed in all the erythroid precursors in the bone marrow of vitamin E-deficient monkeys. Many of these cells were multinucleated. The remainder of the marrow elements appeared normal. Reasons for considering the anemia to be primarily due to inadequate erythropoiesis are given. Serum iron, glutathione stability of the erythrocytes, hemoglobin electrophoresis, osmotic fragilities and platelet counts were all found to be normal in the vitamin E-deficient monkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Animal studies have observed the development of severe anaemia and morphological abnormalities of the bone marrow among primates on long-term vitamin E-de®cient diets 130,131 . Treatment with vitamin E stimulated reticulocytosis and improved blood parameters among these animals 132 . Abnormal erythropoiesis, impaired iron metabolism and decreased erythrocyte survival times have also been observed in vitamin E-de®cient animals 130,133,134 .…”
Section: Vitamin Ementioning
confidence: 86%
“…Animal studies have observed the development of severe anaemia and morphological abnormalities of the bone marrow among primates on long-term vitamin E-de®cient diets 130,131 . Treatment with vitamin E stimulated reticulocytosis and improved blood parameters among these animals 132 . Abnormal erythropoiesis, impaired iron metabolism and decreased erythrocyte survival times have also been observed in vitamin E-de®cient animals 130,133,134 .…”
Section: Vitamin Ementioning
confidence: 86%
“…Experimental induction of vitamin E deficiency in Maeaea [asdeularis, Cebus alb/frons and Cebus apella resulted in a progressive macrocytic haemolytic anaemia together with other features of vitamin E deficiency which were not necessarily related to the anaemia and which included skeletal muscle degeneration (Ausman & Hayes, 1974;Hayes, 1974). Experimental induction of vitamin E deficiency in rhesus monkeys (Macaca mulatta) also induced an anaemia and a muscular dystrophy (Dinning & Day, 1957;Porter, Fitch & Dinning, 1962;Fitch et al, 1965) and it was concluded that the anaemia was due to impaired production as well as decreased life span of red blood cells. Skeletal muscle myopathy has also been produced in squirrel monkeys (Saimiri sciureus) by selenium deficient diets (Muth, Weswig, Whanger & Oldfield, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Two possible explanations for this are: the defect could be shared by all erythroid cells including reticulocytes, but be apparent only in the more immature erythroid precursor because it normally synthesizes thirty times as much porphyrin as the reticulocyte (Table 1); or, those cells that leave the bone marrow as reticulocytes and get into the peripheral blood could have been able to synthesize porphyrin in normal amounts throughout their maturation. In support of the latter possibility is the fact that mature erythrocytes from deficient animals are not hypochromic or microcytic (Porter et al 1962) as would be expected if haemoglobin synthesis in these cells had been defective. This possibility might also help explain the high bone marrowfree protoporphyrin concentrations in the deficient animals.…”
Section: Discussionmentioning
confidence: 90%
“…Decreased porphyrin synthesis could not be correlated with the degree of the characteristic morphologic abnormality of the erythroid cell of the vitamin E-deficient monkey (Porter et al 1962). Some fluorescent cells were present in the incubated bone marrow samples from deficient animals and fluorescence was seen in a few multinucleated erythroid precursors as well as in the more normal appearing ones.…”
Section: Porphyrin Synthesismentioning
confidence: 81%